2008
DOI: 10.1209/0295-5075/82/29001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic boundary conditions on the dynamo threshold of von Kármán swirling flows

Abstract: Abstract. -We study the effect of different boundary conditions on the kinematic dynamo threshold of von Kármán type swirling flows in a cylindrical geometry. Using an analytical test flow, we model different boundary conditions: insulating walls all over the flow, effect of sodium at rest on the cylinder side boundary, effect of sodium behind the impellers, effect of impellers or side wall made of a high magnetic permeability material. We find that using high magnetic permeability boundary conditions decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 21 publications
5
55
0
Order By: Relevance
“…Either or both mechanisms could be significant in the VKS dynamo. Gissinger et al (2008) found using a numerical model of VKS that both ferromagnetic disks and ferromagnetic blades decreased the threshold for dynamo action. Gissinger (2009) presented results of numerical simulations of VKS using a kinematic code, which by taking into account both the axisymmetric mean of the flow and its non-axisymmetric components could generate either an axial dipole or axial quadrupole.…”
Section: The Influence Of Boundariesmentioning
confidence: 98%
“…Either or both mechanisms could be significant in the VKS dynamo. Gissinger et al (2008) found using a numerical model of VKS that both ferromagnetic disks and ferromagnetic blades decreased the threshold for dynamo action. Gissinger (2009) presented results of numerical simulations of VKS using a kinematic code, which by taking into account both the axisymmetric mean of the flow and its non-axisymmetric components could generate either an axial dipole or axial quadrupole.…”
Section: The Influence Of Boundariesmentioning
confidence: 98%
“…This procedure has been proposed in two papers by Iskakov et al [24,25], and was recently modified and applied to various dynamo problems [26,27]. We will present this method in some more detail, since it seems to be most efficient for the simulation of dynamo problems in arbitrary domains.…”
Section: Treating the Boundary Conditions For Non-spherical Domainsmentioning
confidence: 99%
“…The parameter σ div in (27) is chosen very small as it is a measure for the divergence the velocity solution is allowed to have. The parameter σ pen in (28) determines the trade-off between minimizing the mean squared residual deviation of the observed fields and minimizing the kinetic energy of the estimated velocity field.…”
Section: Inverse Problems At Low Rmmentioning
confidence: 99%
“…(b) Measurements of the induced axial magnetic field by BC-effect for a transverse applied field along the x-axis with both counter-rotating discs in von Kármán experiment, from Bourgoin et al (2004a) ferential rotation, and the effect has been accurately treated in several numerical simulations (Bourgoin et al 2004b;Stefani et al 2006;Xu et al 2008). Inhomogeneities in the magnetic boundary conditions, which appear to favour dynamo action ) have been considered in numerical studies (Avalos-Zuniga and Plunian 2005; Gissinger et al 2008) but need to be probed in more details experimentally.…”
Section: Electrical Boundary Conditionsmentioning
confidence: 99%